EXPLORATORY FISHING EXPERIMENTS IN HIRAKUD RESERVOIR -ORISSA STATE (1967-70) - GEORGE, V C; NAIDU, R M; KUNJfPALU, K K (Fishery Technology, 2016)
Suitable areas for fishing have been lccated in the middle andupper regions of the Mahanadi course of Hirakud reservoir. Inthe former the suitable period is during summer and beginning ofmonsoons, and in the latter in summer and winter months. Thefishery of the reservoir is contributed by four species namely S. silo_ndia, L. fimbriatus, C. mirgala and C. catla.